'Rational use of high‐flow therapy in infants with bronchiolitis. What do the latest trials tell us?' A Paediatric Research in Emergency Departments International Collaborative perspective. (3rd July 2019) - O'Brien, Sharon; Craig, Simon; Babl, Franz E; Borland, Meredith L; Oakley, Ed; Dalziel, Stuart R; ,
Abstract: Bronchiolitis is the most common reason for infants to be hospitalised. Over the past decade, the use of high‐flow nasal cannulae (HFNC) therapy has increased markedly and it is now utilised not only in the intensive care unit setting but in general paediatric wards and emergency departments. The aim of this systematic review was to summarise and critique the current evidence‐base for the use of HFNC in infants with bronchiolitis. We searched Ovid Medline, OvidEmbase, PubMed, Cinahl, Cochrane Library, Cochrane Database of Systematic Reviews and Cochrane Central Register of Controlled Trials for systematic reviews and randomised controlled trials of HFNC therapy in infants with bronchiolitis from 1 January 2000 to 27 June 2018. We identified four randomised controlled trials ( n = 1891) of HFNC in infants with bronchiolitis: three of these studies involved infants treated in emergency departments and inpatient paediatric wards in Spain, Australia and New Zealand, and one study involved infants treated in paediatric intensive care units in France. The findings of this review suggest that HFNC should be used as a rescue treatment for hypoxaemic infants who have not responded to standard sub nasal oxygen therapy. The use of HFNC for work of breathing in the absence of hypoxaemia, and severe disease, is not currently supported by the evidence, and should only be considered in the context of an appropriate research trial.